Perception, knowledge level and barriers to reproductive behaviour among community women in selected local government areas (LGAs) of Oyo State, Nigeria (2014)
Reproductive behaviour is important in the life of every household as it reflects on their reproductive anatomy. In Nigeria and other parts of the world, women were not given opportunities to speak on matters concerning their own lives, they were vulnerable; and this militated against them. The study adopted the descriptive research design of expo facto type. The target population consisted of community women who have been married for at least three years in marital life. A Multistage sampling procedure was adopted for the study. A snow ball sampling technique was used to select 1300 respondents. A self-designed questionnaire called Reproductive Health Behaviour Scale was the main instrument used for data collection which was complimented by key in-depth interview (KB). Data was analysed using frequency counts, percentages and bar charts. Findings showed that, majority of the respondents have adequate knowledge of and different methods of reproductive health. The study also identified barriers to effective women reproductive health knowledge and behaviour among women. Based on these findings, recommendations were made that information on reproductive health rights of women should be provided and that cultural and traditional religious injunctions should be discouraged